THE CORRELATION BETWEEN AI (ARTIFICIAL INTELLIGENCE) AND STUDENTS’ SPEAKING PERFORMANCE IN THE EFL CLASSROOM - Pebriani, Yelta; Riswanto; Serasi, Reko (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
The aim of this study is to investigate whether there is a correlation between the use of artificial intelligence and the speaking performance of fourth-semester English department students at Universitas Islam Negeri Fatmawati Sukarno Bengkulu. To achieve this goal, the study selected a sample of 40 students from the same department and employed a quantitative method with a correlational analysis technique. The data was gathered through a set of questionnaires consisting of 20 questions, which were distributed to the students. The responses were rated on a Five Likert Scale to assess students' speaking performance levels. Additionally, the study conducted an oral test for five groups of students to assess their speaking skills in five aspects: grammar, vocabulary, fluency, pronunciation, and comprehension. The analysis of the data using the Product-Moment Pearson Correlation revealed that students did not achieve higher speaking performance scores despite using AI. The calculation yielded a total rxy of -.258, with N. sig = .109, indicating that tcount was less than ttable (-.258 < 0.312). This result supports the acceptance of the null hypothesis, suggesting that there is no significant correlation between AI use and speaking performance of fourth-semester English department students at Universitas Islam Negeri Fatmawati Sukarno Bengkulu.